2008
DOI: 10.1016/j.bbabio.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

An ancient look at UCP1

Abstract: Brown adipose tissue serves as a thermogenic organ in placental mammals to defend body temperature in the cold by nonshivering thermogenesis. The thermogenic function of brown adipose tissue is enabled by several specialised features on the organ as well as on the cellular level, including dense sympathetic innervation and vascularisation, high lipolytic capacity and mitochondrial density and the unique expression of uncoupling protein 1 (UCP1). This mitochondrial carrier protein is inserted into the inner mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 46 publications
1
43
0
1
Order By: Relevance
“…To investigate whether adipogenic differentiation is a feature shared by tumor cells in clinical prostate cancer progression and bone metastasis, we examined adipogenic marker expression in a total of 45 human prostates by IHC assays. Here we present our findings regarding UCP1, an adipogenic marker exclusive to brown fat cells (27) that we found to be induced in prostate cancer cells (Figure 2). …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…To investigate whether adipogenic differentiation is a feature shared by tumor cells in clinical prostate cancer progression and bone metastasis, we examined adipogenic marker expression in a total of 45 human prostates by IHC assays. Here we present our findings regarding UCP1, an adipogenic marker exclusive to brown fat cells (27) that we found to be induced in prostate cancer cells (Figure 2). …”
Section: Resultsmentioning
confidence: 81%
“…Similarly, FABP4/aP2 was constitutively expressed, while LPIN1 was seen at a lower level and was induced transiently around 4 days of the induction (Figure 2B). Interestingly, the expression of UCP1, a brown adipocyte-specific gene functioning to uncouple energy metabolism (27), was induced 4 days into adipogenic induction (Figure 2B). These results thus revealed that prostate cancer cells could express adipocyte-specific markers both constitutively and after adipogenic induction.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, brown adipocytes dissipate energy in the form of heat upon β-adrenergic stimulation. This process is mediated by uncoupling protein 1 (UCP1), a protein residing in the inner mitochondrial membrane, uncoupling the proton motive force of the respiratory chain, thereby combusting energy as heat (Klingenspor et al, 2008).…”
Section: Adipose Tissue Depotsmentioning
confidence: 99%
“…The four gene families involved in mitochondrial transport also represent an evolutionary cluster (Figure 1): SLC25, with 43 members (the largest of all SLC families), is known to comprise the ‘mitochondrial carriers’, shuttling a variety of metabolites across the mitochondrial inner membrane;68 and UCP1,69 UCP270,71 and UCP370 (located at chromosomes 4q28-q31, 11q13 and 11q13.4, respectively) function as ancient uncoupling proteins, or proton pumps involved in mitochondrial energetics (Table 1). …”
Section: Transport Across Mitochondrial Membranesmentioning
confidence: 99%